Provision of Medical-psychological and Psychiatric Care to Patients with Post-covid Syndrome in Telemedicine Conditions (Bangladesh Journal of Medical Science, 2022)
Objective. The need for scientific understanding of the revolutionary changes that have occurred associated with the situation of the COVID-19 pandemic, both in the organization of psychological and psychiatric care, and in the direction of developing effective treatment and prevention measures, determines the relevance of this study, the purpose of which is to study the clinical manifestations of psychopathological symptoms in patients, survivors of the COVID-19 disease, and develop a conceptual model for providing them with medical care in telemedicine.Materials and methods. We studied the psychopathological manifestations of post-covid syndrome in 129 patients who had recovered from COVID-19 and who applied to us for remote medical counseling psychological and psychiatric help for 10 months, from March to December 2020, using clinical psychopathological and psychodiagnostic test research methods.Results and Discussion. The high level of stress, anxiety and depression identified in the studied patients is primarily associated with the negative situation of the pandemic and the COVID-19 disease. A follow-up study proved the effectiveness of a treatment carried out in a telemedicine setting and combining cognitive-behavioral therapy with antidepressants and non-benzodiazepine tranquilizers. In patients who underwent a severe form of COVID-19, in the presence of premorbid chronic bronchopulmonary pathology, in addition to long-lasting psychopathological symptoms, somatic post-covid complications were also observed, and the stressfulness of the situation was perceived at a deeper personal level. For such patients, the course of treatment in telemedicine conditions should be extended and medical and psychological support provided during the entire period of convalescence.Conclusion. Chronic premorbid diseases of the bronchopulmonary and immune systems are predictors of long-term psychopathological symptomatology and the occurrence of post-covid somatic complications. The treatment tactics of patients with post-covid mental health disorders in telemedicine should be based on the protocols of cognitive-behavioral therapy for hypochondriacal and generalized anxiety disorder, in combination with antidepressants and tranquilizers of the non-benzodiazepine series, which ensures the stability of the positive results of therapeutic interventions, confirmed by our studies. The conceptual patientcentered model developed by us for the provision of psychological and psychiatric care for post-covid syndrome in telemedicine can be recommended as a universal algorithm for psycho-psychiatric interventions when providing remote assistance to patients with post-covid mental disorders.Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 719-730